2006
DOI: 10.1037/0022-0663.98.2.420
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phonological processing and inattentive behavior on reading acquisition.

Abstract: This article reports the findings from a longitudinal study investigating the influence of phonological processing and inattentive behavior on reading acquisition. Data from individually administered measures of phonological processing and reading, as well as teacher ratings of children's behavior, were collected from a cohort of 132 children at 12-month intervals, from kindergarten to 2nd grade. Results from multiple linear regression analyses employing latent constructs of phonological abilities and inattent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 52 publications
11
90
0
6
Order By: Relevance
“…This result seems to reflect the cross-sectional association found in numerous studies between inattention and word reading achievement in elementary school children (Billard et al, 2009;Dally, 2006;Giannopulu et al, 2008;McGee et al, 2002;Rabiner & Coie, 2000;Roy & Rutter, 2006). Reading difficulties were shown to be more strongly associated with the inattentive subtype of ADHD (Giannopulu et al, 2008;Hinshaw, 1992;Lundervold, Heimann & Manger, 2008;Willcutt & Pennington, 2000a) and the association between conduct problems and reading difficulties was mediated by co-morbid ADHD (Carroll et al, 2004;Willcutt & Pennington, 2000b).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…This result seems to reflect the cross-sectional association found in numerous studies between inattention and word reading achievement in elementary school children (Billard et al, 2009;Dally, 2006;Giannopulu et al, 2008;McGee et al, 2002;Rabiner & Coie, 2000;Roy & Rutter, 2006). Reading difficulties were shown to be more strongly associated with the inattentive subtype of ADHD (Giannopulu et al, 2008;Hinshaw, 1992;Lundervold, Heimann & Manger, 2008;Willcutt & Pennington, 2000a) and the association between conduct problems and reading difficulties was mediated by co-morbid ADHD (Carroll et al, 2004;Willcutt & Pennington, 2000b).…”
Section: Discussionmentioning
confidence: 51%
“…Children from families characterized by low parental education levels and a family history of reading difficulties might be at increased risk of developing co-morbid reading difficulties and attention problems, due to the well established interference of inattentive behavior in reading acquisition (Dally, 2006), especially in disadvantaged environments (Velting & Whitehurst, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is supported by a study in which data of phonological processing and reading, as well as teacher ratings of child behavior, was collected from children from kindergarten to 2nd grade (N=132). The analysis of the relationships among the variables indicated that inattentiveness negatively affected the acquisition of PA skills (5) . On the other hand, it has been reported that children with ADHD without learning disabilities do not present PA difficulties.…”
Section: Introductionmentioning
confidence: 99%